Progress in the application of epimedium and its major bioactive components in the treatment of orthopedic diseases - Tong, Dan; Chen, Long; Jiang, Zeyi; Ye, Xuxia; Ma, Mengjie; Ye, Angzhi; Xu, Jian (Frontiers in Pharmacology, 2025)
Epimedium brevicornu (Yin Yang Huo), a widely used traditional Chinese medicinal ingredient, has garnered significant attention for its role in treating orthopedic diseases such as osteoporosis. Our work through network pharmacology and bioinformatics analysis, we identified that out of 27 major active components in Epimedium brevicornu, 8 key components have therapeutic effects on 11 types of diseases related to orthopedic conditions. The disease-target association analysis indicated that Osteoarthritis, Osteoporosis, Muscle Spasm and Myopathy have relatively clear targets for disease treatment. The KEGG enrichment analysis results indicate that the signaling pathway of Epimedium treatment in Osteoarthritis may be closely related to the Lipid and atherosclerosis pathway, PPAR signaling pathway and Arachidonic acid metabolism. Epimedium may treat osteoporosis with Nitrogen metabolism, GABAergic synapse, and Pathways in cancer. Epimedium may affect muscle spasticity through Neuroactive ligand-receptor interaction, Serotonergic synapse and Cholinergic synapse closely related to nervous system function; Additionally, our analysis suggests that Epimedium may treat myopathy through Nitrogen metabolism and GABAergic synapse pathways. These studies have not only provided a molecular mechanism-based explanation for the pharmacological effects of Epimedium, but also laid a theoretical foundation for the development of Epimedium-based precision therapeutic regimens.